The Effect of Financial Literacy, Fintech Exposure, Accounting Information, and Investor Psychology on Investment Decisions - Herijawati, Etty; Wi, Peng (Institut Bisnis dan Informatika Kesatuan, 2025)
Rapid advancements in digital financial services have transformed how individuals access, process, and respond to investment information, yet the combined effects of financial literacy, fintech exposure, accounting information, and investor psychology on investment behavior remain insufficiently explained. This study aims to examine how these factors shape investment decisions, with investment interest functioning as a mediating variable. Using a quantitative cross-sectional approach, data were obtained from 300 active investors through structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares. The results show that all four determinants significantly and positively influence investment decisions both directly and indirectly through investment interest, with fintech exposure emerging as the strongest predictor. The proposed model accounts for 72% of the variance in investment interest and 78% of the variance in investment decision quality. These findings underscore the importance of integrating financial education, psychological preparedness, and digital literacy within fintech ecosystems to strengthen investor engagement and enhance decision-making quality.